Ethnobotany of Traditional Medicine of The Sasak Bayan Tribe, Anyar Village, North Lombok - Reza Wariani; Muhlis Muhlis; I Gde Mertha (Jurnal Biologi Tropis, 2023)
This research was used to determine the number of plant species used in traditional medicine, the parts of the plants used, the method of processing, and their properties for treating diseases used by the Sasak Bayan Tribe in Anyar Village, North Lombok. The subjects in this study were the Sasak people living in Bayan, Anyar Village, North Lombok. Respondents in this study consisted of 10 people with an age range of 40-102 years. Techniques in collecting data consists of 3 ways, namely interviews, observation, and documentation. The technique in analyzing data consists of 3 techniques, data reduction, data display, and conclusions. The data information obtained shows that there are 36 species from 26 families that are used to cure diseases in Anyar Village, North Lombok. The parts of the plant used as medicine include flowers, roots, tubers, rhizomes, fruit, leaves, stems, and mucus. There are various ways to process plants as medicine, including boiling, grating, pounding, pressing, cooking vegetables, using directly, squeezing, slicing, anointing, brewing, dripping, smearing, chewing and pasting. Various diseases can be treated by utilizing plants by the Sasak Tribe in Anyar Village, North Lombok which consists of 32 diseases.